1964
DOI: 10.1192/bjp.110.464.56
|View full text |Cite
|
Sign up to set email alerts
|

Haloperidol: A Controlled Clinical Trial in Chronic Disturbed Psychotic Patients

Abstract: Haloperidol is a drug that fulfils Delay's criteria of a neuroleptic in that:1.It inhibits psychomotor agitation without producing sleep.2.Alleviates psychomotor manifestations.3.Produces with increasing dosage characteristic extrapyramidal signs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1965
1965
2013
2013

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In the study already mentioned Okashu and Tewfik (1964) direct attention to what is probably an important source of error in controlled placebo trials on chronic schizophrenic patients. They point out that their results agree with those of Rotbstein et al (1962) who found that in a population of 18 chronic schizophrenics in the environment of a quiet ward, 11 could be withdrawn from tranquillizing medication for up to six months without showing adverse effects.…”
Section: )mentioning
confidence: 99%
“…In the study already mentioned Okashu and Tewfik (1964) direct attention to what is probably an important source of error in controlled placebo trials on chronic schizophrenic patients. They point out that their results agree with those of Rotbstein et al (1962) who found that in a population of 18 chronic schizophrenics in the environment of a quiet ward, 11 could be withdrawn from tranquillizing medication for up to six months without showing adverse effects.…”
Section: )mentioning
confidence: 99%